A study of relationship between cardiac exposure dose-volume and cardiovascular autonomic dysfunction in radiotherapy - CHEN Hongyu, SU Pengyu, LUO Wenzi, PANG Dequan, WANG Feiran (Zhongguo aizheng zazhi)
Background and purpose: The incidence of autonomic dysfunction (AD) in patients with advanced cancer is approximately 65%-80%. The neurasthenic symptoms such as dizziness, palpitations and fatigue caused by AD are difficult to alleviate even with sufficient rest, seriously affecting the patients’ quality of life. Meanwhile, the cardiovascular autonomic nervous system plays a significant regulatory role in heart rate, myocardial function and myocardial blood flow. AD increases the morbidity and mortality risk of cardiovascular diseases in patients. AD is not only a functional state but might also be an early sign of overall myocardial lesion. Research indicates that after adjusting for age, gender and cardiovascular risk factors, previous radiation exposure is associated with AD manifestations such as increased resting heart rate and abnormal heart rate recovery after exercise. However, there are currently few relevant studies on the effect of radiotherapy on cardiac autonomic function, and the specific injury effects and dose threshold of injury occurrence remain unclear. This study aimed to explore the impact of thoracic radiotherapy on the cardiac autonomic function of patients with malignant tumors by comparing the differences in heart rate variability (HRV) analysis parameters before and after radiotherapy, and to explore the dosimetric risk factors for the occurrence of AD by comparing the dosimetry between the case group and the control group, providing a theoretical basis for optimizing the dose distribution of radiotherapy regimens in order to improve patient prognosis and reduce the occurrence of complications. Methods: We prospectively collected data of patients with malignant tumors who underwent thoracic radiotherapy in the Radiotherapy Department of the Affiliated Hospital of North China University of Science and Technology from February 2023 to December 2023. Inclusion criteria: ① Patients who were pathologically confirmed to have malignant tumors (lung cancer breast cancer or esophageal cancer); ② patients with radiation therapy indications as recommended by the guidelines; ③ patients with an ECOG score of 0-1; ④ patients with no significant abnormalities in electrocardiogram and echocardiography results. Exclusion criteria: ① previously received chest radiotherapy; ② patients with obvious palpitation, chest tightness and chest pain before treatment; ③ diabetes, heart disease and other serious underlying diseases; ④ anti-arrhythmic drugs are currently being used; ⑤ patients who cannot tolerate radiotherapy and who were lost or lost during follow-up. HRV analysis was used to evaluate changes in autonomic nerve function after radiotherapy. Patients with AD were included in the case group, and the remaining patients were included in the control group. Univariate and multivariate logistic regression analysis methods were used to explore the dosimetric risk factors and cardiac dose limitations for the occurrence of AD after thoracic radiotherapy. This study was approved by the ethics committee of Affiliated Hospital of North China University of Science and Technology (ethics number: 20230228020). Results: A total of 89 patients with thoracic tumors meeting the study criteria were enrolled in the study. Among them, 41 (46%) patients experienced cardiac AD after radiotherapy. The cardiac Dmax (6 273.500 cGy vs 4 675.900 cGy, P<0.001), cardiac Dmean (1513.700 cGy vs 452.050 cGy, P<0.001), cardiac V5 (49.000% vs 21.250%, P<0.001), V20 (30.500% vs 7.300%, P<0.001), V30 (18.700% vs 3.600%, P<0.001) and V40 (10.900% vs 1.500%, P<0.001) were significantly higher in the case group than in the control group. The results of multivariate logistic regression analysis showed that cardiac V30 was an independent risk factor for the occurrence of cardiac AD[OR (95% CI)=1.583 (1.093-2.291), P=0.015]. Cardiac V30 could predict the occurrence of radiation-induced cardiac injury with an area under the curve of 0.788, and 17.1% was the optimal cut-off value of cardiac V30 for predicting the occurrence of cardiac AD. Conclusion: After thoracic radiotherapy, the cardiac irradiation dose-volume was significantly higher in patients with cardiac AD than in the control group. When cardiac V30 was higher than 17.1%, the risk of cardiac AD in patients significantly increased.